DISPENSASI KAWIN AKIBAT HAMIL DI LUAR PERKAWINAN DAN DAMPAKNYA PADA FORMULASI PIDANA ZINA - Siregar, Thogu Ahmad; Sianturi, Petrus Richard (Faculty of Law, Parahyangan Catholic University, 2020)
Data shows a high number of under-age or child marriages Indonesia. A related phenomenon is number of dispensation requested to the court to conduct marriage in case one or both couples are under age. Reason for this practice may be escape route from poverty, or as a more common justification to prevent sexual intercourse outside marriage (fornication) considered per se immoral. Meanwhile, drafter of the Indonesian Criminal Code decides to criminalize sexual intercourse outside marriage. The author, using a descriptive analytical approach, suggest that, at the abstract level, a contradiction exist between the rule of allowing the granting of court dispensation and the rule purporting to criminalize sex outside marriage. Dispensation, in the final analysis, may be used to de-criminalize sex between under age couples.